(untitled) (Konturen, 2015)
The German mystics were particularly important for Kierkegaard because of the proximity of Germany to Denmark and because of their influence on both German idealism and the Pietist tradition in which Kierkegaard was raised. This article is the first attempt to look at the issue of how the views of the German mystics may have influenced Kierkegaard’s though. It begins with an introduction to what one could call mystical epistemology, but then looks more specifically at the epistemology of two medieval German mystics, Meister Eckhart and Johannes Tauler, and at Kierkegaard’s exposure to the German mystical tradition. Finally, it presents an account of Kierkegaard’s own religious epistemology that makes clear that it is largely indistinguishable from the epistemology of Ekhardt and Tauler.